Comparative Genomic Analysis of the Human Pathogen Wohlfahrtiimonas Chitiniclastica Provides Insight Into the Identification of Antimicrobial Resistance Genotypes and Potential Virulence Traits - Kopf, Anna; Bunk, Boyke; Coldewey, Sina M.; Gunzer, Florian; Riedel, Thomas; Schröttner, Percy (Frontiers in Cellular and Infection Microbiology, 2022)
Recent studies suggest that W. chitiniclastica may be the cause of several diseases in humans including sepsis and bacteremia making the bacterium as a previously underappreciated human pathogen. However, very little is known about the pathogenicity and genetic potential of W. chitiniclastica; therefore, it is necessary to conduct systematic studies to gain a deeper understanding of its virulence characteristics and treatment options. In this study, the entire genetic repertoire of all publicly available W. chitiniclastica genomes was examined including in silico characterization of bacteriophage content, antibiotic resistome, and putative virulence profile. The pan-genome of W. chitiniclastica comprises 3791 genes with 1639 core genes (43%) indicating a putative metabolic conserved species. Furthermore, in silico analysis indicated presumed resistome expansion as defined by the presence of genome-encoded transposons and bacteriophages. While macrolide resistance genes macA and macB are located within the core genome, additional antimicrobial resistance genotypes for tetracycline (tetH, tetB, and tetD), aminoglycosides (ant(2'')-Ia, aac(6')-Ia ,aph(3'')-Ib, aph(3')-Ia, and aph(6)-Id)), sulfonamide (sul2), streptomycin (strA), chloramphenicol (cat3), and beta-lactamase (blaVEB) are distributed among the accessory genome. Notably, our data indicate that the type strain DSM 18708 does not encode any additional clinically relevant antibiotic resistance genes, whereas drug resistance is increasing within the W. chitiniclastica clade. This trend should be monitored with caution. To the best of our knowledge, this is the first comprehensive genome analysis of its kind, providing new insights into the genome of this opportunistic human pathogen.